New Education Policy 2020: Problems and Solutions - Aanshik Shukla (Knowledgeable Research A Multidisciplinary Journal, 2025)
The New Education Policy 2020 is the education policy of India which was announced by the Government of India on 29 July 2020. This is the first major change in the education policy of India after the New Education Policy released in 1986. This policy is based on the report of the committee headed by space scientist K. Kasturirangan. Education in India is not only a means of individual development, but it is also the foundation of social, economic and national progress. The New Education Policy 2020 (NEP 2020) is a historic initiative of the Government of India, which has been presented after 34 years with the aim of bringing comprehensive reforms in the education sector. It aims to create an inclusive, flexible, multidimensional and skill-based education system. However, along with many positive aspects of this policy, many challenges and controversial points have also emerged in its implementation. This research paper has done a detailed analysis of the basic features of NEP 2020, major problems and their possible solutions.